Sugarcane yield loss due to water and nitrogen deficiencies evaluated by carbon isotopic discrimination method - Kölln, Oriel Tiago; Gava, Glauber José de Castro; Cantarella, Heitor; Silva, Sérgio Ricardo; Ocheuze Trivelin, Paulo Cesar (Emirates Journal of Food and Agriculture, 2021)
Water and nitrogen (N) availability are determining factors for crop development and production. Assessments of sugarcane yield loss based on these factors may become more accurate by using the stable carbon (C) isotope technique. The aim of this work was to evaluate the effect of N and water on sugarcane yield, isolating the yield losses (YL) caused by N or by water limitations, and correlating them with the fractionation of C isotopes (Δ13C). The research was carried out in field conditions in the municipality of Jaú, Brazil. A statistical design in randomized block was used, considering the 2 ´ 2 ´ 2 factorial arrangement, composed of two cycles [first (2008/09) and second (2009/10)], two N rates (without and with N) and two water supplies (rainfed and irrigated). These variables were evaluated: biometric features (plant height, stalk diameter and tillering), yield elements [stalk yield (STY), sucrose yield (SUY), and stalk dry matter (SDM)], technological quality parameters [fiber content, sucrose juice content (SJC), and total sucrose recovery (TSR)], stalk N concentration (SNC) and accumulation (SNA), and Δ13C. The effect of irrigation associated with N fertilization on STY, SUY, and SDM, resulted in average increases of 53.7, 9.0, and 18.6 Mg ha-1, respectively. The average YL for STY in two crop seasons were 40.5%, 35.2%, and 48.2% due to limitations of N or water or N+water, respectively. The SNC was not affected by the water supply, but it was increased by N fertilization. The highest value of Δ13C was obtained for the treatment without N fertilization in rainfed conditions, and the least Δ13C was found for the one with N supply and irrigation. The Δ13C measurement was effective in identifying N and water deficiencies, presenting potential to be used as an indicator of N and water limitations for sugarcane yield. Keywords: Loss index of stalk biomass; Saccharum ssp.; Water deficit; Water‒N interaction; Water supply